Reconstruction of ancestral plant genomes for inter-crop translational research - Cléa Siguret; Margaux Olivier; Cécile Huneau; Mamadou Dia Sow; Pierre-Louis Stenger; Christophe Klopp; Marie-Laure Martin; Jean-Philippe Tamby; Serguei Gorbounov; Raphael Flores; Fabrice Legeai; Matéo Boudet; et al. (Molecular Plant, 2026)

Meta-analysis reveals contrasting effects of biodegradable and conventional microplastics on earthworm fitness, physiology, and gut microbiota - Hesen Zhong; Jerome Mathieu; Chengshuai Liu; Patrick Lavelle; Jun Dai; Ying Lu; Chi Zhang (Soil Biology and Biochemistry, 2026)

Nationwide operational mapping of grassland first mowing dates combining machine learning and Sentinel-2 time series - Henry Rivas; Hélène Touchais; Vincent Thierion; Jerome Millet; Laurence Curtet; Mathieu Fauvel (Remote Sensing of Environment, 2024)

Growing maize while biological remediating a multiple metal-contaminated soil: a promising solution with the hyperaccumulator plant Sedum alfredii and the earthworm Amynthas morrisi - Chi Zhang; Hesen Zhong; Jerome Mathieu; Bo Zhou; Jun Dai; Mikael Motelica-Heino; Patrick Lavelle (Plant and Soil, 2024)

Persistent organochlorine pesticides in periprostatic adipose tissue from men with prostate cancer: Ethno-geographic variations, association with disease aggressiveness - Jean-Philippe Antignac; Sandy Figiel; Michèle Pinault; Pascal Blanchet; Franck Bruyère; Romain Mathieu; Souhil Lebdai; Georges Fournier; Jerome Rigaud; Karine Mahéo; Philippe Marchand; Ingrid Guiffard; et al. (Environmental Research, 2023)

Glaciation as an historical filter of below‐ground biodiversity - Jerome Mathieu; T. Jonathan Davies (Journal of Biogeography, 2014)
Aim The latitudinal gradient in species richness is one of the most studied biodiversity patterns. Here we explore a north–south gradient in earthworm diversity, and evaluate the importance of current and historical filters in shaping the distribution of present‐day below‐ground species richness. Location France. Methods Using high resolution data on earthworm distributions across France, we document the latitudinal gradients in alpha (α), beta (β) and gamma (γ) diversity. We relate these gradients to species' traits, taxonomic aggregation and co‐occurrence patterns, and correlate them with the present climate and the history of glaciation in Europe. Results We found that γ‐diversity decreases from south to north whereas α‐diversity increases along the same latitudinal gradient. Communities in formerly glaciated regions are composed of smaller, more mobile species and show trait and taxonomical aggregation. In more southerly populations, which did not experience glaciation, earthworm species are larger, have smaller geographical ranges, and communities demonstrate a decrease in species co‐occurrence resulting in lower local species richness. Main conclusions We show that species richness gradients can present different – sometimes opposite – latitudinal trends depending upon the scale of the analysis. This scale dependence sheds new light on the underlying causes of global biodiversity gradients. The opposing latitudinal trends of the different components of diversity suggest that recolonization following glaciations during the Pleistocene acted as an environmental filter, and that competitive exclusion may be a more dominant ecological force in these former refugial areas. Overall our results show that past climate changes have left a deep footprint on present‐day earthworm diversity patterns, from community to macroecological scales, and that different mechanisms of earthworm community assembly may predominate at different latitudes.

Population Pharmacokinetic Analysis of Blood and Joint Synovial Fluid Concentrations of Robenacoxib from Healthy Dogs and Dogs with Osteoarthritis - Hanna E. Silber; Claudia Burgener; Ingrid M. Letellier; Mathieu Peyrou; Martin Jung; Jonathan N. King; Philippe Gruet; Jerome M. Giraudel (Pharmaceutical Research, 2010)

Optimal first feed organism for South African mud crab Scylla serrata (Forskl) larvae - Jerome A. Davis; Mathieu Wille; Thomas Hecht; Patrick Sorgeloos (Aquaculture International, 2005)